TINJAUAN HUKUM EKONOMI SYARIAH TERHADAP PRAKTIK PEMESANAN KARKAS AYAM ANTARA UNIT KITCHEN DENGAN RUMAH PEMOTONGAN AYAM DI AL-ZAYTUN - Ilmar Fandini, Salsabilah; Rojak Samsudin, Agus; Maulana, Rizal (Cahaya Ilmu Bangsa, 2024)
This research examines the practice of ordering chicken carcasses between Kitchen units and Chicken Slaughterhouses in Al-Zaytun based on the perspective of sharia economic law. The main focus is the salam contract mechanism and the conformity of ordering practices with the pillars, terms and principles of sharia. This research aims to identify and evaluate the mechanisms and suitability of ordering practices with sharia economic law. The method used is descriptive qualitative research with a field approach. Data was collected through interviews, observation and documentation studies, then analyzed through data reduction, data presentation and drawing conclusions. The research results show that the greeting contract mechanism for ordering chicken carcasses between the Kitchen and the Chicken Slaughterhouse in Al-Zaytun is procedurally appropriate, from submission to delivery. However, evaluation of the suitability of practices based on the pillars, terms and principles of the salam contract revealed several discrepancies, especially regarding the official halal certification of the slaughterhouse. However, chicken slaughterhouses have implemented sharia standards which include halal, fairness, freedom from maysir, gharar and usury, as well as transparency in the implementation of contracts. Keywords: Chicken Ordering Practices; Contract mechanism; Appropriateness of practice